Теплова інтеграція процесу очищення коксового газу від бензольних вуглеводородів за допомогою програм "Hint" та "Aspen Hysys" - Товажнянський, Леонід Леонідович; Ульєв, Леонід Михайлович; Васильєв, Михайло Анатолійович (НТУ "ХПІ", 2012)
Present work is dedicated to studying of the benzene distillation process and energy saving retrofit of existing flowsheet by process integration methods. Target values of cold and hot utilities of existing process were determined. Hot and cold utilities consumption was reduced on 45 % and 20,2 % respectively. It was achieved by ∆Тmin decreasing and cross pinch blocking. Design of the optimal heat exchangers network design was outlined.
Keywords: енергоресурси; енергозбереження; енергоємність; енергоспоживання; пінч-аналіз; дестиляція бензолу